Anticonvulsant Effect of Quinic Acid in Pentylenetetrazol-induced Seizures in Mice: Investigating the Role of Oxidative Stress Pathway and Nitric Oxide - ‌Behnam Raeisi; Hossein Amini-Khoei; Seyed Mohsen Mortazavi; Mohammad Rahimi-Madiseh; Zahra Lorigooini (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: Epilepsy is a central nervous system disorder in which the activity of nerve cells in the brain is disrupted and leads to seizures. Despite the variety of available anticonvulsant drugs, approximately 30% of patients are resistant to conventional therapies. Nowadays, attention to drugs of natural origin, especially plant sources, has increased. Due to the effects of quinic acid, including antioxidant, anti-inflammatory, hepatoprotective, and immune cell-enhancing properties, this study aimed to determine the anticonvulsant effect of quinic acid in pentylenetetrazole-induced seizures in mice by investigating the possible role of the oxidative stress pathway and nitric oxide. Materials and Methods: In this experimental study, 48 male mice were divided into 6 groups of 8. The first group received PTZ at a dose of 90 mg/kg, the second to fifth groups received quinic acid at doses of 5, 10, 20, and 40 mg/kg, and the sixth group received Diazepam at a dose of 10 mg/kg. One week after quinic acid administration, seizures were induced in all mice by intravenous injection of pentylenetetrazole. Results: Quinic acid at doses of 20 and 40 mg/kg significantly increased seizure threshold compared to the group treated with normal saline (P<0.001). Quinicic acid treatment reduced serum nitrite and malondialdehyde levels of brain tissue (P<0.001). Quinic acid treatment also increased serum and brain tissue antioxidant activity in mice. Quinic acid significantly reduced the expression of iNOS and nNOS genes compared to the normal saline group (P<0.01). Conclusion: Quinic acid seems to have potential anticonvulsant effects. Its mechanism of action is probably to inhibit neuroinflammation and act through the nitric oxide pathway